PREVALENCE AND SENSITIVITY PATTERN OF ESBL PRODUCERS IN DIFFERENT CLINICAL ISOLATES FROM A TERTIARY HEALTHCARE CENTER OF EASTERN INDIA, A CROSS-SECTIONAL STUDY. - Jena, Lipika; Behera, Birsen; Jena, Diptimayee; Singh, Santosh; Panigrahy, Rajashree; Sahu, Kundan Kumar; Kar, Dattatreya; Das, Suren Kumar (Student’s Journal of Health Research Africa, 2024)
Background Antimicrobial-resistant organisms have led to increased mortality, morbidity, and economic burden throughout the globe. This study focused on measuring the prevalence of antimicrobial resistance bacteria mostly by extended-spectrum β-lactamase (ESBL) producers from several samples in a facility providing tertiary care in Eastern Odisha. Methods A cross-sectional study was conducted from February 2021 to January 2022. During that time a total of 2452 culture-positive specimens were processed from different samples. Identification of organisms and antibiotic susceptibility was done manually through Kirby Beuer’s disc diffusion method. Phenotypic detection of ESBL producers was performed by a Double disc synergy test. Results During the study, E. coli (852) was identified as the most prevalent organism followed by S. aureus (661) and K. pneumoniae (301). Among them, 1571 isolates were ESBL-producing and E. coli was the most prevalent one followed by S. aureus and K. pneumoniae which were 659, 479, and 172 in number respectively. Most of the ESBL producers were isolated from urine samples and the least number from stool samples. We found in this study that the highest population of P.mirabilis and K. oxytoca were resistant to the fluoroquinolones group of antibiotics, Pseudomonas and K. oxytoca are highly resistant to aminoglycosides group of antibiotics, P.mirabilis, Enterobacter, P. vulgaris and Enterococci were showing high resistance towards penicillin group of antibiotics, P.mirabilis was highly resistant towards β-lactamase inhibitor group of antibiotics. Conclusion As per the study findings, E. coli is the main producer of ESBLs among members of the Enterobacteriaceae family, and urine is the main source of ESBL-positive isolates. These findings are highly significant from a medical and scientific standpoint and may influence policymakers to better monitor and manage antibiotic resistance.